1978
DOI: 10.1002/polc.5070650113
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the ladder polymer cis‐syndiotactic poly(phenylsilsesquioxane) in solution

Abstract: Studies on the properties of the double‐chain ladder polymer of cis‐syndiotactic poly(phenylsilsesquioxane) (PPSQ) in dilute and concentrated solutions are reported. Data on the intrinsic viscosity [η], the second virial coefficient A2, and the mean‐square radius of gyration 〈s2〉 as functions of molecular weight M, temperature, and solvent lead to the conclusion that the conformation of PPSQ can be modeled with a wormlike chain model with a persistence length ρ of 74 Å. These data cannot be used to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The discussion of experimental procedures is abbreviated here, since detailed discussion of most of these appear elsewhere in this symposium [ 1,2]. Polymers were obtained from three sources: (1) PBO polymers were provided by Dr. F.…”
Section: Methodsmentioning
confidence: 99%
“…The discussion of experimental procedures is abbreviated here, since detailed discussion of most of these appear elsewhere in this symposium [ 1,2]. Polymers were obtained from three sources: (1) PBO polymers were provided by Dr. F.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work on the characterization of carbon nanotubes and other similar structures has generated renewed interest in the transport properties of rodlike particles. [1][2][3][4][5][6][7][8][9][10][11][12] Many of these studies have simply assumed that these structures are rodlike, ignoring observational evidence for finite persistence lengths, or other sources of flexibility. This paper is not concerned with the validity of the rodlike picture for any particular type of particle but instead with the validity of theoretical expressions of the transport properties of rods that are currently in use for the characterization of various nanoparticle structures.…”
Section: Introductionmentioning
confidence: 99%
“…Among these characterization techniques, the a value in the Mark-Houwink equation is repeatedly reported to give values around 1 [13][14][15], implying that PPSQ has random coil to rod-like shapes. In their dilute solution study, Helminiak and Berry concluded that the conformation of PPSQ can be represented with a wormlike chain model with a persistence length of 75Å [16]. Frye and Klosowski strongly opposed the ladder structure and suggested a more or less randomly linked array of polycyclic cages [17].…”
Section: Introductionmentioning
confidence: 99%
“…, and H T 3 16 cage molecules using gas chromatography, 1 H and 29 Si NMR, elemental analysis, and mass spectrometry. Synthesis and identification of compounds with the structures of…”
Section: Introductionmentioning
confidence: 99%